To the history of diocesan council in Saratov (1918–1920) - Mramornov Aleksandr (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
The history of beginnings and functioning of the diocesan council in Saratov eparchy of the Russian Orthodox Church, one of the largest in Volga region, is represented in this article basing upon discovered sources. Basic biographical facts about the members of the council is given; most important decisions of the council, the history of the show trial against the council’s members, the issue of transfer of aff airs to bishop’s offi ce in 1920 are also discussed.